The use of acoustic collars for studying landscape effects on animal behavior - Lynch, Emma, author; Angeloni, Lisa, advisor; Wittemyer, George, advisor; Crooks, Kevin, committee member; Fristrup, Kurt, committee member (Colorado State University. Libraries, 2013)
Audio recordings made from free-ranging animals can be used to investigate aspects of physiology, behavior, and ecology through acoustic signal processing. On-animal acoustical monitoring applications allow continuous remote data collection, and can serve to address questions across temporal and spatial scales. We report on the design of an inexpensive collar-mounted recording device and present data on the activity budget of wild mule deer (Odocoileus hemionus) derived from these devices, which were applied for a two-week period. Over 3,300 hours of acoustical recordings were collected from 10 deer on their winter range in a natural gas extraction field in northwestern Colorado. Results demonstrated that acoustical monitoring is a viable and accurate method for characterizing individual time budgets and behaviors of ungulates. This acoustical monitoring technique also provides a new approach to investigate the ways external forces affect wildlife behavior. One particularly salient activity revealed by our acoustical monitoring was periodic pausing by mule deer within bouts of mastication, which appear to be adopted for listening for environmental cues of interest. While visual forms of vigilance, such as scanning or alert behavior, have been well documented across a wide range of animal taxa, animals also employ other vigilance modalities such as auditory vigilance, by listening for the acoustic cues of predators. To better understand the ecological properties that structure this behavior, we examined how natural and anthropogenic landscape variables influenced the amount of time that mule deer paused during mastication bouts. We found that deer paused more where concealment cover abounded, and where visual vigilance was likely to be less effective. Additionally, deer paused more often at night than they did during the day, and in areas of moderate background sound levels. Our results support the idea that pauses during mastication represent a form auditory vigilance that is responsive to landscape variables. Furthermore, these results suggest that exploring this behavior is critical to understanding an animal's perception of risk and the costs associated with vigilance behavior.
Keywords: acoustic monitoring; behavior; energy development; mule deer; sound recording; wildlife